Innovative on-farm solar dryer for paddy - Abhinav Dubey; P.K. Sharma (Annals of Agricultural Research, 2023)
Food grains are generally harvested at moisture content of 18-25% (wb) whereas safe storage of cereals occurs at nearly 13-14% (wb) and pulses at 7-8% (wb). Thus excess moisture in harvested grains needs to be removed in short time. A Solar powered air inflated grain dryer was developed at ICAR-IARI, New Delhi with inflatable drying chamber. The drying chamber was made up of UV stabilized top transparent sheet and bottom thick polythene sheet. A solar operated DC Axial fan (dia. 40 cm) was used for blowing unit. The moisture reduction time of 22-14% in 100 kg of paddy (PB 1121) was found to be 7.5-9 hours. The total cost of the dryer was Rs. 10850. Thus the Solar powered air inflated grain dryer is a low cost portable dryer which is manufactured using easily available materials and can eliminate all the disadvantages occurring in the sun drying.